100 Soruda Yabancı Dil Olarak Türkçe Öğretimi - Acemoğlu, Adil; Oryaşin, Utku; Güven, Ahmet Zeki; Okur, Alpaslan; Demirdöven, Gökhan Haldun; Bölükbaş Kaya, Fatma; Demirel, Mehmet Volkan; Özden, Esra; Akkaya, Mehmet; Şengül , Ladin; Dönmez, Ayhan; İşci Karameşe, Cenan; et al. (2023)
-